Furrow-like invaginations of the yeast plasma membrane correspond to membrane compartment of Can1 - Strádalová, Vendula; Großmann, Guido (Journal of cell science, 2009)
Skip to Next Section Plasma membrane of the yeast Saccharomyces cerevisiae contains stable lateral domains. We have investigated the ultrastructure of one type of domain, the membrane compartment of Can1 (MCC). In two yeast strains (nce102Δ and pil1Δ) that are defective in segregation of MCC-specific proteins, we found the plasma membrane to be devoid of the characteristic furrow-like invaginations. These are highly conserved plasma membrane structures reported in early freeze-fracture studies. Comparison of the results obtained by three different approaches - electron microscopy of freeze-etched cells, confocal microscopy of intact cells and computer simulation - shows that the number of invaginations corresponds to the number of MCC patches in the membrane of wild-type cells. In addition, neither MCC patches nor the furrow-like invaginations colocalized with the cortical ER. In mutants exhibiting elongated MCC patches, there are elongated invaginations of the appropriate size and frequency. Using various approaches of immunoelectron microscopy, the MCC protein Sur7, as well as the eisosome marker Pil1, have been detected at these invaginations. Thus, we identify the MCC patch, which is a lateral membrane domain of specific composition and function, with a specific structure in the yeast plasma membrane - the furrow-like invagination.